microRNAs to Monitor Pain-migraine and Drug Treatment - Gallelli, Luca; Cione, Erika; Caroleo, Maria C.; Carotenuto, Marco; Lagana, Pasqualina; Siniscalchi, Antonio; Guidetti, Vincenzo (MicroRNA, 2017)
Background: Migraine is a prevalent neurovascular disorders with a complex pathophysiology and therapeutic options characterized by important side effects or problems related to drug abuse. No specific biomarkers are recognized to be univocal for this subclinical condition, yet. In this concern microRNAs (miRNAs) have been suggested as potentially useful screening/diagnostic tool, and research is underway to recognize the most effective candidate(s). In this concern in the present review we Herein we highlighted miRs involvement in pain and migraine, as well as drug response and efficacy focusing also on miRs panel results from mice model with multiple induced pain conditions, and human patients with migraine in order to understand if there are similar miRs expression pattern may useful into human translational studies. Results: During human migraine attack specific miRs were found dysregulated, as well as in mouse models with different pain conditions. Amongst all the miRs screened in mice/human suffering of pain the miR-590-5p was found alterated. This latter miR, in mice is modulated by celecoxib, while in human is dysregulated in the complex regional pain syndrome, condition where migraine assume a risk factor for its development. Recently has been reported that pharmacological treatments, indirectly can pertubate miRNA expression results. Therefore, miR-590-5p could assume an interesting double meaning for a clinical point of view. It can be considered biomarker of general pain, including migraine and also biomarker to evaluate the efficacy of the drug treatment. This could be of great importance in infant-juvenile segment, where the diagnosis of migraine is very challenging. In this view, since therapy is often started with NSAIDs herein we discuss also how the discovery of the new role of miRNAs in determining drug efficacy open a new scenario in the pain-migraine tailored therapy and pharmacogenomics concept. Conclusion: miRNAs could have a pleiotropic meaning in the clinical management of migraine and could represent biomarkers of pathology, of drug efficacy as well as drug adherence to the treatment.
Keywords: microRNA